On Butterflies and Silences: Exploring Teachers' and Students' Experiences in High School Biology Classrooms - Sharon Pelech (University of Calgary, 2019)
This paper is a hermeneutic inquiry into how students and teachers experience the biology classroom and how they navigate between expectations from external factors leading to classrooms that are focused on memorizing facts and the desire to engage students deeply in the discipline of biology. From data collected from semi-structured interviews with teachers and students, and an open-ended questionnaire, the paper explores the experiences and assumptions about teaching biology that is prevalent in the classroom. The inability of teachers or students to be able to point to memorable experiences within the classroom leads to a discussion of students’ experience of biology as a passive transmission of facts that are often considered irrelevant and boring. The paper explores the teachers’ sense of conflict between wanting to instill a love for biology in their students and their perceived role in preparing students to memorize information for tests and prepare students for post-secondary school.